2019
DOI: 10.1016/j.ymthe.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Mediated Progranulin Delivery to a Mouse Model of Progranulin Deficiency Causes T Cell-Mediated Toxicity

Abstract: Adeno-associated virus-mediated gene replacement is emerging as a safe and effective means of correcting single-gene mutations affecting the CNS. AAV-mediated progranulin gene (GRN) delivery has been proposed as a treatment for GRNdeficient frontotemporal dementia and neuronal ceroid lipofuscinosis, and recent studies using intraparenchymal AAV-Grn delivery to brain have shown moderate success in histopathologic and behavioral rescue in mouse models. Here, we used AAV9 to deliver GRN to the lateral ventricle t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 56 publications
(81 reference statements)
1
48
0
Order By: Relevance
“…Physical methods such as microinjection, 68,69 microfluidic, 70,71 sonication, 72,73 centrifugation, 74 cellular deformation, 75 laser irradiation 76,77 or electroporation 78,79 induce or facilitate cell entry of vectors by mechanical force, mainly through disrupting the plasma membrane. They are commonly applied in non-viral gene delivery because they transport the genetic information easily without the need for carriers and the otherwise low infectivity.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Physical methods such as microinjection, 68,69 microfluidic, 70,71 sonication, 72,73 centrifugation, 74 cellular deformation, 75 laser irradiation 76,77 or electroporation 78,79 induce or facilitate cell entry of vectors by mechanical force, mainly through disrupting the plasma membrane. They are commonly applied in non-viral gene delivery because they transport the genetic information easily without the need for carriers and the otherwise low infectivity.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Several therapeutic options are being explored to overcome progranulin haploinsufficiency 19 . A major strategy is to directly enhance progranulin expression level using gene therapy vectors introduced into the medial prefrontal cortex (mPFC) 20,21 , although one study showed that overexpression of GRN in Grn KO mice led to neurodegeneration 22 . Increased progranulin level can also be achieved by enhancing global transcriptional activity using histone deacetylase (HDAC) inhibitors 23,24 or by activating autophagy with trehalose 25 .…”
mentioning
confidence: 99%
“…As such, efforts to increase progranulin production in patients are underway [62][63][64][65]. However, a more recent study has suggested that progranulin delivery to brain promotes in T-cell infiltration and neuronal and glial degeneration [66]. Progranulin cleavage and granulin levels were not measured in these studies, and may account for differences in the observed results.…”
Section: Discussionmentioning
confidence: 99%